2015
DOI: 10.1038/onc.2015.278
|View full text |Cite
|
Sign up to set email alerts
|

Effects of p21-activated kinase 1 inhibition on 11q13-amplified ovarian cancer cells

Abstract: p21-activated kinases (PAKs) are Cdc42/Rac–activated serine-threonine protein kinases that regulate of several key cancer-relevant signaling pathways, such as the Mek/Erk, PI3K/Akt, and Wnt/b-catenin signaling pathways. Pak1 is frequently overexpressed and/or hyperactivated in different human cancers, including human breast, ovary, prostate, and brain cancer, due to amplification of the PAK1 gene in an 11q13 amplicon. Genetic or pharmacological inactivation of Pak1 has been shown to reduce proliferation of dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
35
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(37 citation statements)
references
References 40 publications
2
35
0
Order By: Relevance
“…An advanced member of this series, FRAX1036 (PDB ID:5DFP), exhibits high PAK1 potency (PAK1 Ki = 23 nM), refined kinome selectivity [42, 46, 47], and represents a useful tool compound for single and combinatorial experimental therapeutics [42, 4648]. However, all of these early FRAX compounds were found to have strong adverse inhibition of hERG potassium channels.…”
Section: Atp-competitive Pak1 Inhibitorsmentioning
confidence: 99%
See 2 more Smart Citations
“…An advanced member of this series, FRAX1036 (PDB ID:5DFP), exhibits high PAK1 potency (PAK1 Ki = 23 nM), refined kinome selectivity [42, 46, 47], and represents a useful tool compound for single and combinatorial experimental therapeutics [42, 4648]. However, all of these early FRAX compounds were found to have strong adverse inhibition of hERG potassium channels.…”
Section: Atp-competitive Pak1 Inhibitorsmentioning
confidence: 99%
“…Such “signalopathies” include several tumorigenic disorders, primarily cancers associated with PAK1 amplification [8, 47]. Positioned downstream of difficult-to-target oncogenes such as RAS, PAK1 might open a new window for disruption of RAS-driven tumorigenesis [11, 38, 64].…”
Section: Conclusion and Prospectsmentioning
confidence: 99%
See 1 more Smart Citation
“…Table 2 summarizes the SAR of aminopyrazole analogs with various substituted 4-azaindole tails (7)(8)(9)(10). Modeling indicated that extending the (S)-a-methyl vector might be tolerated due to the large degree of flexibility in the glycine-rich loop in the PAK1 kinase domain.…”
mentioning
confidence: 99%
“…In recent years there have been several studies suggesting therapeutic potential of small molecule PAK1 inhibitors in breast cancer cell lines 8 and in ovarian cancers that are characterized by PAK1 gene amplification. 9 To date, no PAK inhibitor has advanced to proof-of-concept studies in human. A PAK1 selective inhibitor would be a valuable tool compound to test the efficacy and safety associated with inhibiting group 1 PAK isoforms.…”
mentioning
confidence: 99%